2006
DOI: 10.1002/jrs.1546
|View full text |Cite
|
Sign up to set email alerts
|

Polarized IR, spontaneous and stimulated Raman spectra of Y(HCOO)3·2H2O single crystal — a new Raman laser material

Abstract: Polarized Raman and IR spectra have been measured for Y(HCOO) 3 ·2H 2 O single crystal at room temperature. Assignment of the observed bands to the respective internal and external vibrations was proposed on the basis of factor group approach for the orthorhombic P2 1 2 1 2 1 (D 4 2 ) space group and the literature data for the other metal formates. The results obtained for the spontaneous Raman scattering have been used in the discussion of the stimulated Raman spectra of the material studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…the C-H stretching mode (ν1), the symmetric (ν2) and antisymmetric C-O stretching mode (ν4), the symmetric OCO bending mode (ν3) as well as the C-H in-plane (ν5) and C-H out-of-plane 8 bending mode (ν6) [24]. The isolated EtA + cation has Cs symmetry and its 27 internal modes are distributed among the irreducible representation: Γ= 16A'+11A" [25].…”
Section: Vibrational Propertiesmentioning
confidence: 99%
“…the C-H stretching mode (ν1), the symmetric (ν2) and antisymmetric C-O stretching mode (ν4), the symmetric OCO bending mode (ν3) as well as the C-H in-plane (ν5) and C-H out-of-plane 8 bending mode (ν6) [24]. The isolated EtA + cation has Cs symmetry and its 27 internal modes are distributed among the irreducible representation: Γ= 16A'+11A" [25].…”
Section: Vibrational Propertiesmentioning
confidence: 99%
“…www.lpr-journal.org [318,374] heterodesmic organic crystals with predominantly ionic bonds between structural units [743,756,806] heterodesmic organic crystals with predominantly van der Waals bonds between structural units a) Self-SRS (SHG), i.e. SRS from the SHG arising from the pumping (fundamental) radiation.…”
Section: Nonlinear Crystalline Materials For Laser Raman Convertersmentioning
confidence: 99%
“…Even at 10 K we did not observe any of the skeletal modes suggested by Kartha and Venkateswaran. [13] Also, none of them was observed by Maczka et al [5] ; the lowest wavenumber vibration observed for Y(HCOO) 3 · 2H 2 O is around 100 cm −1 . Here we observed for La(HCOO) 3 six vibrations at 125, 151, 175, 213, 240 and 263 cm −1 .…”
Section: Resultsmentioning
confidence: 93%
“…There are several papers discussing the structural, thermal, magnetic and optical properties of the RE(HCOO) 3 compounds and their deuterated analogs. [1 -4] For instance, Maczka et al [5] have investigated the infrared (IR), spontaneous and stimulated Raman spectra of the Y(HCOO) 3 ·2H 2 O formate, which is a new and promising Raman laser material. Recently, Bohaty et al [6] have investigated the mechanical, thermo-mechanical and piezoelastic properties of the Y(HCOO) 3 · 2H 2 O and Er(HCOO) 3 · 2H 2 O formates.…”
Section: Introductionmentioning
confidence: 99%